The long-term effects of the context/keyword and rote methods on the receptive and productive learning of ELF vocabulary - Rivas, Jesús; Rodriquez, Máximo (Lenguas Modernas, 2017)
This paper reports on an experiment in which the long-term effects of the rote and the combined context/keyword methods on the receptive and productive leaming of 15 English nouns by a group of college EFL learners were compared. Participants' receptive and productive recall were assessed eithcr immediately after the lreatment or a week later. The results showed that both methods were equally effective in enhancing recall of the Spanish word given its English equivalent (receptive recall), but that rote ied to superior recall of English equivalents of Spanish words (productive recall). Lack of an optimal time to create and rehearse the images and students' maturity and expcrience as EFL learners are discussed as possible factors diminishing the effect of the context/ keyword method.